PERILAKU MASYARAKAT DALAM MEMBUANG SAMPAH KE KONTAINER SAMPAH DI KELURAHAN BATUNG TABA NAN XX KECAMATAN LUBUK BEGALUNG, KOTA PADANG - Iftitah Iftitah Rahmi; Deded Chandra (JURNAL BUANA, 2023)
This study aims to: (1) find out how the behavior of the people of Batung Taba Nan XX Village, Lubuk Begalung District in disposing of waste and (2) find out whether the distance of waste containers from their homes affects the behavior of the people of Batung Taba Nan XX Village, Lubuk Begalung District in disposing of waste. rubbish. The type of research in this research is a mixed method research (combined research). By utilizing primary data and secondary data. Primary data was obtained from questionnaire data analysis, direct interviews with the community in Batung Taba Nan XX Village, and stakeholders related to the data needed in the study. Secondary data were obtained from the Padang City Environmental Service (DLH) and the Padang City Central Statistics Agency (BPS). Data collection techniques in this study were using observation techniques, questionnaires or questionnaires, and documentation, using data analysis techniques, namely data reduction analysis. This research shows that: (1) The behavior of the community in disposing of waste into garbage containers in Batung Taba Nan XX Village, Lubuk Begalung District from data analysis shows that the results are not good, this is evidenced by the amount of garbage in open land, garbage in rivers, garbage burned, garbage in the sewers and garbage on the side of the road; (2) the distance of the garbage container from the residence based on the results of data analysis shows that it affects the behavior of the community in disposing of waste in Batung Taba Nan XX Village, Lubuk Begalung District, this is evidenced by the behavior of residents who prefer to dispose of waste to places that are considered effective, not charged and close to the neighborhood where the community lives.